The neutronics effect of TRISO duplex fuel packing fractions and their comparison with homogeneous thorium-uranium fuel - Rabir M.H.; Ismail A.F.; Yahya M.S. (John Wiley and Sons Ltd, 2023)
Fuels; High temperature reactors; Thorium; Uranium; Burn up; Cycle length; Fuel rods; High-temperature reactor; Long cycles; Micro modular reactor; Modular reactors; Packing fractions; Thorium reactor; TRISO-duplex; Doppler effect